A preliminary investigation of M3DITRACK3R: A medicine dispensing mobile robot for senior citizens - Chelvam, Y.K. (Elsevier B.V., 2014)
Medicine adherence among patients is crucial to ensure the effectiveness of a given treatment. Failure to take a medication of the right dosage, at the right time causes minor healthcare problems to become worse. This is extremely problematic for the elderly patients who have difficulties in keeping track of their medicine. Therefore, to address this issue, M3DITRACK3R, an automated medicine dispenser which keeps track of the dosage and duration between each consumption, autonomously navigate to the patient and dispensing the medicines to the patient is proposed. This innovative prototype is able to detect its patient using sensing technology. Number of touch detected by the touch sensor is used to set the number of hours in each loop. M3DITRACK3R then navigates to find the patient using the infrared sensor to dispense the right dosage of medicine at the right time. It is a perfect solution for senior citizens living independently. Â© 2014 The Authors.